2009
DOI: 10.1007/978-3-642-03655-2_77
|View full text |Cite
|
Sign up to set email alerts
|

Fair Partnerships – Working with NGOs

Abstract: Abstract. This paper highlights how Non-Governmental Organizations (NGOs) can be utilized during the design of Information Communication Technologies for Development (ICT4D). We use the design process of a voter education system as a case study, which incorporated three NGOs from two African countries. Of key interest to us are the ways in which we can avoid exploiting these NGOs and make sure the ICT intervention meets their goals, as well as those of the researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Because their work often requires interactions with governmental agencies, NGOs frequently have insight and knowledge regarding national or regional orientations in policy-making (Delisle et al 2005, 3). According to Gitau and Mardsen (2009), NGO partners can help align research programmes and initiatives with national health policies, potentially increasing the sustainability of the research programmes. Due to their longer-term presence in communities, NGOs may also be well placed to support the establishment of cooperative relationships and acceptance by local communities for research projects (Gitau and Mardsen 2009, 704-707).…”
Section: Increased Access To Communities and Governmental Representatmentioning
confidence: 99%
“…Because their work often requires interactions with governmental agencies, NGOs frequently have insight and knowledge regarding national or regional orientations in policy-making (Delisle et al 2005, 3). According to Gitau and Mardsen (2009), NGO partners can help align research programmes and initiatives with national health policies, potentially increasing the sustainability of the research programmes. Due to their longer-term presence in communities, NGOs may also be well placed to support the establishment of cooperative relationships and acceptance by local communities for research projects (Gitau and Mardsen 2009, 704-707).…”
Section: Increased Access To Communities and Governmental Representatmentioning
confidence: 99%
“…However, these views broadened the concept of One Device Per Child, where Device can be a mobile phone, tablet, or laptop. The provision of the device should be accompanied with high-quality interaction design, whilst considering a community's cultural beliefs and attitudes (Gitau and Marsden 2009). For instance, mechanisms should be integrated into a shared device to protect individual users' privacy, while respecting the culture of sharing upheld by the community to which the users belong (Sambasivan et al 2018).…”
Section: Hci4d: One-device-per-child With Quality Interaction Design ...mentioning
confidence: 99%
“…These NGOs acted as intermediaries to members of the DLM (workers and employers). We chose to work with the NGOs because of previous researches which have shown that NGOs serve as human access points to the community and help in understanding the situation on the ground (Gitau & Marsden, 2009). They have also been shown to be important as mediating agents both for communication and avoiding marginalization (Madon & Sahay, 2002;Eevi Beck, Madon & Sahay, 2004).…”
Section: The Overall Study Objectivementioning
confidence: 99%